The photodissociation dynamics of ozone at 226 and 248 nm: O(³PJ) atomic angular momentum polarization - Brouard, M; Goman, A; Horrocks, S; Johnsen, A; Quadrini, F; Yuen, W (American Institute of Physics, 2007)
Speed distributions, and spatial anisotropy and atomic angular momentum polarization parameters have been determined for the O(³PJ) products following the photodissociation of ozone at 248 and 226 nm using velocity map ion imaging. The data have been interpreted in terms of two dissociation mechanisms that give rise to fast and slow products. In both cases, excitation is believed to occur to the B˜ state. Consistent with previous interpretations, the speed distributions, translational anisotropy parameters, and angular momentum polarization moments support the assignment of the major pathway to curve crossing from the B˜ to the repulsive R˜ surface, generating fast fragments in a wide range of vibrational states. For the slow fragments, it is proposed that following excitation to the B˜ state, the system crosses onto the A˜ state. The crossing seam is only accessible to molecules that are highly vibrationally excited and therefore possess modest recoil speeds. Once on the A˜ state, the wavepacket is thought to funnel through a conical intersection to the ground state. The velocity distributions, spatial anisotropy parameters, spin-orbit populations and polarization data each lend support to this mechanism.